BEHAVIOR IN THE USE OF THE APPLICATION SYSTEM IN SHARIA FINANCING SAVING AND LOAN COOPERATIVES IN EAST JAVA - Hidayat, Ujang Syaiful (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This research is motivated by the low interest in using application software in KSPPS in East Java, the researchers suspect that many factors cause this, including due to less than optimal usage training, the time available to perform or use the software. The training and time spent by KSPPS management have a very big influence. In this study , examines whether there is a relationship between interest and the method of applying an application program by the KSPPS Management in East Java . This study uses a systematic literature review (SLR) method or literature study. The results of the study can be seen that (1) the time of using the application program must adjust the time of the KSPPS management, (2) In applying the program it must be accompanied or learning to implement the program, (3) in using the system there must be a strong intention in using the system to implement the program. application in KSPPS in East Java. Furthermore, suggestions in this study are expected to the management in this case the management to provide learning time in implementing the program. Then it is expected that other researchers can relate other variables that affect program implementation.